Microbial fuel cell is emerging as a versatile technology: a review on its possible applications, challenges and strategies to improve the performances - Kumar, Ravinder; Singh, Lakhveer; Zularisam, A. W.; Faisal, Alamri (John Wiley and Sons Ltd, 2018)
Microbial fuel cells (MFCs) are emerging as a versatile renewable energy technology. This is particularly because of the multidimensional applications of this eco-friendly technology. The technology depends on the electroactive bacteria,popularly known as exoelectrogens, to simultaneously produce electric power and treat wastewater. Electrodemodi fications with nanomaterials such as gold nanoparticles and iron oxide nanoparticles or pretreatment methods such as sonication and autoclave sterilization have shown promising results in enhancing MFC performance for electricity generation and wastewater treatment. The MFC technology has been also investigated for the removal of various heavy metals and toxic elements, and to detect the presence of toxic elements in wastewater. In addition, the MFCs can be modified into microbial electrolysis cells to generate hydrogen energy from various organic matters. This article provides a comprehensive and state-of-the-art review of possible applications of the MFC technology. This also points out the various challenges that limit MFC performance. Finally, this article identifies the strategies to improve MFC performance for different applications.